Disruptores endócrinos em chorume: estudo de caso do aterro controlado de Divinópolis/MG - Araújo, Bruna Martins Nogueira (2015)
The impact caused by the increasing production of waste, as well as its proper treatment and disposal, have caused much concern regarding the release of toxic organic compounds that are discarded into the environment. Among the waste generated, landfill leachate is highlighted as a potential pollution issue for surface and groundwater, presenting high values of biochemical oxygen demand - BOD, chemical oxygen demand - COD, and the presence of endocrine disruptors. Therefore, the aim of this research was conducting a case study of the landfill leachate produced by municipal solid waste - MSW in the Controlled Landfill in Divinópolis, Minas Gerais, Brazil, as well as verifying the presence of Endocrine Disruptors in it, and promoting the importance of a proper environmental management of MSW. A data survey was conducted in Divinópolis – MG and the landfill leachate was sampled at the local geographic coordinates of 20° 08' 44" S and 44º 53' 01' W. Subsequently, a solid phase extraction (SPE) was performed previously to the identification of the organic compounds by gas chromatography coupled to mass spectrometry (GC/MS). By means of the survey, we verified large amounts of putrescible organic matter, plastic and paper. Among the possible EDs present in the slurry, we could identify dioctylphthalate (DOP), bisphenol A (BPA) and diethyl phthalate (DEP). In summary, it was possible to conduct a survey regarding the generation and treatment of the MSW in the Controlled Landfill of the municipality. Based on the observation of these contaminants, despite the quantification of the EDs had not being feasible, it became reasonable to discuss the technologies involved in removing and in the effective manners in which to treat these micropollutants, clearing an immense study field in the environmental area.